IMPLEMENTASI TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI ANTAR PESERTA DIDIK SEKOLAH MENENGAH PERTAMA - Iin Aulia Nurun Nisa; Siti Khomairoh; Ainun Aisyah (STKIP Subang, 2026)
21st-century education emphasizes the importance of communication, collaboration, critical thinking, and creativity skills to prepare the Indonesia’s Golden Generation 2045 or widely known as Generasi Emas Indonesia 2045. One of the skills that needs to be developed is collaboration, because through teamwork, students can learn to appreciate others opinions, taking responsibilities, and actively contribute to completing shared tasks between students. This study aims to improve students’ collaboration skills through the implementation of the Teams Games Tournament (TGT) learning model. The subjects of this research were 31 eighth-grade students of SMP Negeri 11 Samarinda in the 2024/2025 academic year. The method used was Classroom Action Research based on the Kemmis and McTaggart model, consisting of one cycle including planning, action implementation, observation, and reflection. Data were collected through observation and documentation, then analyzed quantitatively to measure collaboration skills and qualitatively to describe the learning process. The results showed an increase in collaboration skills from the pre-cycle condition, where only 16% of students were in the collaborative category, to the 64% high at the end of the cycle. Students showed improvement in many aspects of teamwork, active participation, appreciation of different opinions, and group responsibilities. The study concludes that the implementation of the Teams Games Tournament model is effective in improving students collaboration skills. It is recommended that teachers should prepare heterogeneous group formation, assign group leaders, and manage time effectively to optimize the implementation of the TGT model.